An Interval Throwing Program for Baseball Pitchers Based upon Workload Data - Michael M. Reinold; Brittany Dowling; Glenn S. Fleisig; Leonard C. Macrina; Kevin E. Wilk; John T. Streepy; James R. Andrews (International Journal of Sports Physical Therapy)
# Background